An Investigation of ELT Students’ Preferences on the Use of Multimedia Resources in Extensive Listening Activities - M. Usamah Bin Kholil (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study investigates the preferences of English Language Teaching (ELT) students regarding the use of multimedia resources in extensive listening activities. Utilizing a mixed-method approach with an Explanatory Sequential Design, the research combines quantitative descriptive statistics and qualitative thematic analysis to identify the most frequently used multimedia tools and the reasons behind students' choices. The participants consisted of 57 ELT students from Al-Qolam University.Findings reveal that songs and movies are the most preferred multimedia resources. These materials are favored due to their engaging nature and ability to blend entertainment with learning, which helps enhance vocabulary acquisition and improve pronunciation. The repeated exposure to authentic language in songs and movies contributes significantly to students’ listening comprehension and language development. Moderately preferred media include English lessons, game walkthroughs, vlogs, and podcasts, reflecting students' interest in diverse and real-world content. These types of multimedia offer practical language input in various contexts, although they are not as engaging as songs and movies for most students. In contrast, radio programs, sleep stories, and interviews were found to be the least preferred, primarily due to their lack of visual stimuli and perceived monotony, which leads to decreased engagement. Students’ reasons for their preferences were categorized into several key themes: personal interest, fun and entertaining learning experience, motivation to improve vocabulary, and enhanced pronunciation. These findings indicate that students are more likely to engage with and benefit from listening activities that align with their personal interests and offer enjoyable experiences. The study concludes that incorporating enjoyable and student-centered multimedia resources in listening activities can significantly improve motivation, engagement, and language outcomes. It highlights the need for educators to thoughtfully select multimedia materials that resonate with students’ interests to support more effective and meaningful language learning experiences.